THE THE EFFECT OF UNDERSTANDING OF ACCOUNTING, REFORM TAXATION, TAXING SOCIALIZATION, AND TAXATION SANCTIONS TOWARDS OBLIGATION OF TAXATION OBLIGATIONS IN TAX SERVICE OFFICES LISTED AT REGION OFFICES IN THE DIRECTORATE GENERAL OF NORTH SUMATRA TAX I - Wahyuni, Rizka (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to analyze the influence caused by accounting understanding variables, tax administration reforms, tax socialization and tax sanctions on corporate taxpayer compliance at the tax service office registered at the Regional Office of the Directorate General of North Sumatra tax I. This research uses convenience sampling technique with a sample of 100 corporate taxpayers that obtained by using the calculation of the Slovin formula. The data collection technique in this study is a questionnaire, while the data analysis technique used is multiple linear regression analysis processed with the help of the SPSS program. From the results of tests that have been carried out, the simultaneous regression test (Test F) shows that all independent variables studied have a simultaneous influence on the variable of corporate taxpayer compliance. Partial regression test (t test) shows that accounting understanding partially has positive and significant effect on corporate taxpayer compliance, tax administration reforms partially has positive and significant effect on corporate taxpayer compliance, taxation socialization partially has positive and significant effect on taxpayer compliance agency, and taxation sanctions partially have a positive and significant effect on compliance with corporate taxpayers.